THE INFLUENCE OF THE COMPENSATION AND TRAINING TOWARD EMPLOYEE PERFORMANCE AT BNI 46 MANADO BRANCH - Sangkay, Revel; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Banking had a significant influence on the world to set circulation of money. Bank itself have a general function as a place to keeping the money and borrowing money. The things that make a bank can survive is the performance of the employees of the bank. factors that affect the performance of employees include the compensation and training. The objective of the study is to know the influence of the compensation and training toward employee performance at BNI 46 Manado branch. Data was analyzed quantitatively and through use of statistical package for social scientists (SPSS). The research method that used associative analysis with multiple regression analysis using saturated sampling with the sample of the respondents is 79 samples of all the employees at BNI 46 Cabang Manado. The result of this study shown that compensation and training have a significant influence on employee performance at BNI 46 Cabang Manado. For the company in this case BNI 46 Manado branch, it’s recommended to keep enhancing the training, because the variable have a significant influence to employee performance. And for the compensation have a influence but not significant to employee performance. So the compensation needs to improve, because the compensation also determine the performance from the employee to achieve their goal. Keywords: compensation, training, employee performance